Epistemologi Terjemahan Koroang Mala’bi: Kajian atas Edisi Revisi Al-Qur’an Bahasa Mandar - Muhammad Taufiq (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2025)
This study offers an epistemological appraisal of Koroang Mala’bi’ (revised 2019) by examining three pillars: (1) its reference sources, (2) the translation techniques employed, and (3) the accuracy of the final text. The research is library-based; primary data consist of the revised juz 30 and a focused interview with the translator, Muh. Idham Khalid Bodi, while secondary data are drawn from classical and modern tafsir works, Mandar dictionaries, and previous studies. Findings show that the revision still relies chiefly on Tafsīr Jalālayn, Tafsir al-Azhar, and the 2002 Indonesian Ministry of Religious Affairs (MoRA) translation, supplemented by 930 footnotes extracted from the MoRA 2019 edition. Idham adopts a predominantly ḥarfiyyah (word-for-word) approach, shifting to a tafsīriyyah (interpretive) mode only when literal rendering becomes opaque in Mandar. In terms of accuracy, most verses are precise, yet several key terms—such as ḥisāb and qalam—are rendered inconsistently. Overall readability is satisfactory, although a few verses require re-reading due to overlapping synonyms or typographical errors. Linguistic naturalness is generally high, aided by culturally embedded terms like Puang Allah Taala and allo kiama’, but several untranslated borrowings remain unfamiliar to lay readers. The study recommends compiling a standardized glossary, conducting systematic proofreading, and adding brief glosses to enhance the intelligibility of regional-language Qur’ān translations.